HEART DISEASE (COMPLAIN) IN THE QURAN FROM SAYYID QUTTUB'S PERSPECTIVE AND PSYCHOLOGICAL ANALYSIS - Marwan Halim; Katimin; Muhammad Roihan (RADJA PUBLIKA, 2024)
The fulfillment of a person's needs in facing the welfare of life makes people often complain, so that the person becomes weak and empty of faith, as conveyed by Sayyid Quthb in his interpretation, and this is a problem that interests the author to discuss the problem: (1) How does Sayyid Quttub interpret QS Al-Maarij [70]: 19? (2) How is Sayyid Quttub's opinion unique about QS Al-Maarij [70]: 19 viewed from a psychological perspective? The objectives of this research are as follows: (1) To understand Sayyid Quttub's interpretation of QS Al-Maarij [70]: 19. (2) To understand the psychological significance of Sayyid Quttub's opinion on QS Al-Maarij [70]: 19. (3) To understand the psychological significance of Sayyid Quttub's opinion on QS Al-Maarij [70]: 19: 19. In this research, a qualitative research method was used which is a research approach that focuses on a deep understanding of an object, and which notes the importance of someone maintaining their faith by not making an object weak or an object that forgets gratitude and patience, and making complaining a weapon that is not worthy of being used except when they can only complain about their situation to Allah alone with the hope that only Allah can help with all the problems that a person may experience.